POSISI SANKSI DAN DENDA PAJAK DALAM ISLAM PADA INDONESIA SEBAGAI NEGARA HUKUM - Almaidah; Kiki Sriwahyuni; Ice Hardaningsih H (Indonesian Journal of Taxation and Accounting, 2024)
A country that is not yet prosperous or has not been able to finance the development of its own civilization must be supported by its peoples. For example, Indonesia is implementing Self-Assesment tax collection system to facilitate its management. This qualitative research with descriptive explanation seeks to see the position of tax sanctions and fines in Islam in Indonesia as a state of law. As a country based on law, Indonesia must also be seen from the plurality of its population, which is dominated by Muslims. In the taxation system, Islam views that there are several main conditions that make taxes mandatory. In addition, its implementation must tend to the interests of Muslims. However, adaptation is needed to achieve the benefit of all Indonesian people. Based on the results of the research found, the position of Islamic law in viewing tax sanctions and fines was identified as supporting the implementation that had been designed by the state. Every form of violation is an attempt to harm the state which will then have an impact on the general public. Each regulation that has been designed requires support to achieve the interests of the Indonesian people, especially Muslims.